Management of Electrocuted Major Burns in District Hospital - Khoo, Kah Seng; Leong, Qi Wen; Ho, Choon Aik; Lim, Chen Hong (IIUM Medical Journal Malaysia, 2019)
Electrical burns are one of the important health burdens throughout the world with incidences varying between 4–18% of all burns. We are presenting a case of 45-year-old gentleman whom sustained a high voltage electrical injury (railway voltage) with 25% total body surface area (TBSA) of mixed partial burns over the path of current. He was managed primarily by general surgical team in a district hospital. Subsequently, he was discharged home well after 23 days of hospitalization. In this article, we discuss about management of electrocuted burns in district hospital setting without burn unit.